Supporting Sustainable Futures in Retail: An Exploratory Study on Worker Health, Safety and Wellbeing in Australia (2023)
Health, safety, and wellbeing (HSW) have been studied widely in different contexts and are associated with social, organisational, and human sustainability. However, there is limited research about HSW in retail that includes both workers and managers to offer a more holistic and inclusive perspective. To fill this gap, this exploratory and descriptive cross-sectional study employed a 21-item quantitative and 3-item qualitative online survey and engaged a representative sample of 271 workers and 109 managers/owners in Australia. The results showed retailers provide a reasonably adequate technical and social work environment, and workers perceive their job tasks as averagely challenging. Nevertheless, workers still experienced adverse HSW effects frequently, partially attributed to a poor organisational environment. Workers and managers were markedly aligned regarding the current HSW status in Australian retail and agreed that health and safety were not focal areas of their businesses. Worryingly, both groups viewed the unfavourable impacts of work as inescapable, indicating a commonly shared fatalistic perspective that does not align with sustainability practices. Although workers appreciated their employment-related benefits, they also acknowledged that their HSW was not fully supported, presenting unique opportunities for the workplace and policymakers to address such issues and support the economic and social sustainability of retailers.